The Role of Pharmacists in Improving Treatment Adherence and PatientOutcomes among Diabetic Patients (The Review of Diabetic Studies, 2024)
Diabetes mellitus affects approximately 8.5% of the global population and poses a substantial economic burden in the United States, where 25% of healthcare expenditures are attributed to diabetes management. Effective diabetes care is crucial for preventing complications that significantly diminish quality of life, including macrovascular and microvascular issues. Given the challenges of providing comprehensive diabetes management amidst shortages of healthcare providers, pharmacists have emerged as essential members of the diabetes care team. This study explores various pharmacist-managed diabetes care models, highlighting their roles in patient education, therapeutic recommendations, and chronic disease management through collaborative drug therapy management (CDTM) agreements. The article reviews educational interventions, telemanagement approaches, and the integration of technology in enhancing patient care and adherence. It provides evidence that pharmacist interventions lead to significant improvements in glycemic control, demonstrated by average reductions of 1% to 2% in A1c levels. Through team- based and telehealth frameworks, pharmacist-led diabetes management not only improves patient outcomes but also enhances the overall health system’s efficiency by addressing medication adherence and facilitating regular patient followup. This analysis emphasizes the vital contribution of pharmacists in the evolving landscape of diabetes care, advocating for their greater involvement in multidisciplinary healthcare teams to optimize patient outcomes.